GERAK YANG MENDIDIK: Pengembangan Kemampuan Sosial dan Emosional Anak Usia Dini melalui Latihan Motorik di Tiga Model TK di Kota Pekanbaru - Herlina; Saipuddin; Syarifuddin; Hanafi, Imam (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the contribution of motor movement exercises to the development of emotional skills in early childhood at three kindergartens in Pekanbaru City, namely TK Al-Ubudiyah (Islam-based), TK Melayu Fathrizk Kids (general-based), and TK Bintang Madani (Islam–general integration-based). The research uses a qualitative approach with a multi-site study design. Data were collected through participatory observation, in-depth interviews, and documentation of teachers, principals, and parents. Data analysis was conducted thematically through stages of data reduction, open coding, categorization, and inductive conclusion drawing, with validity tested through source and technique triangulation. The results show that motor exercises significantly contribute to the formation of children's emotional competence through contextual learning mechanisms. At TK Al-Ubudiyah, religious motor activities foster internalized courage to express oneself with manners and self-regulation values. At TK Melayu Fathrizk Kids, traditional games promote empathy through direct experience. Meanwhile, at TK Bintang Madani, thematic motor activities and mini outbound activities enhance concentration, independence, and collaborative skills while reducing dependence on gadgets. These findings indicate that a variety of contextual and value-based motor approaches contribute to the holistic development of children's emotional balance.